Battle on the Wrong Field? Entrant Type, Dominant Designs, and Technology Exit - Chen, Tianxu; Qian, Lihong; Narayanan, Vadake (Strategic Management Journal, 2017)
[Research summary: Startups often compete with diversifying entrants in the technology race to define dominant designs, which can be platform technology-based or non-platform technology-based. However, little research has examined the relative risk of technological exits for startups vs. diversifying entrants in such “dominance battles.” We develop a contingency framework that links a firm’s technology exit to its pre-entry experience and the characteristics of the dominance battle. With a sample of 134 technologies involved in 31 dominance battles in the information technology industry from 1979 to 2007, we show that technologies of startups were more likely than those of diversifying entrants to exit from platform technology-based dominance battles; however, this relationship did not exist in non-platform technology-based dominance battles, or after the emergence of dominant designs. Managerial summary:How can a startup that tries to create a dominant design strategize to survive the fierce technology race? This study demonstrates that choosing the right battlefield is of paramount importance. Two aspects of a battlefield are shown as relevant: the type of technology and the stage of industrial evolution. Our results show that technologies sponsored by startups tend to have higher exit rates than those sponsored by diversifying entrants in dominance battles characterized by platform technologies, but this penalty is not evident in dominance battles characterized by non-platform technologies or after the emergence of dominant designs. Furthermore, our study suggests that lack of organizational legitimacy, complementary assets, and integrative capabilities may explain why startups have a higher risk of technology exit than diversifying entrants.]